Highly Efficient Transfection of Human THP-1 Macrophages by Nucleofection - Maeß, Marten B. (J Vis Exp, 2014)
Macrophages, as key players of the innate immune response, are at the focus of research dealing with tissue homeostasis or various pathologies. Transfection with siRNA and plasmid DNA is an efficient tool for studying their function, but transfection of macrophages is not a trivial matter. Although many different approaches for transfection of eukaryotic cells are available, only few allow reliable and efficient transfection of macrophages, but reduced cell vitality and severely altered cell behavior like diminished capability for differentiation or polarization are frequently observed. Therefore a transfection protocol is required that is capable of transferring siRNA and plasmid DNA into macrophages without causing serious side-effects thus allowing the investigation of the effect of the siRNA or plasmid in the context of normal cell behavior. The protocol presented here provides a method for reliably and efficiently transfecting human THP-1 macrophages and monocytes with high cell vitality, high transfection efficiency, and minimal effects on cell behavior. This approach is based on Nucleofection and the protocol has been optimized to maintain maximum capability for cell activation after transfection. The protocol is adequate for adherent cells after detachment as well as cells in suspension, and can be used for small to medium sample numbers. Thus, the method presented is useful for investigating gene regulatory effects during macrophage differentiation and polarization. Apart from presenting results characterizing macrophages transfected according to this protocol in comparison to an alternative chemical method, the impact of cell culture medium selection after transfection on cell behavior is also discussed. The presented data indicate the importance of validating the selection for different experimental settings.